Voltammetric study of a sulfur contaminant of aviation biokerosene - Falone, Max Fabrício [UNESP]; Buffon, Edervaldo [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Springer Nature, 2020)
Butanethiol is a contaminant of aviation biokerosene, and its monitoring is of great importance to evaluate the quality of this biofuel. In this work, the elucidation of the electrochemical behavior of butanethiol was carried out using a glassy carbon electrode in order to contribute to the development of future electroanalytical methods to determine this contaminant in aviation biokerosene. The results obtained showed that the electrooxidation of butanethiol is controlled by diffusion and occurs irreversibly in two steps: a well-defined anodic peak at 1.2 V vs. Ag/AgCl (3.0 mol L−1) and an ill-defined anodic wave at 1.4 V vs. Ag/AgCl (3.0 mol L−1). The Randles-Sevcik and Tafel equations were used to determine the diffusion coefficient (D) and electronic transfer coefficient (α), respectively. In addition, the mechanism of the butanethiol oxidation reaction was proposed based on the number of protons and electrons involved. Good linear relations were obtained between peak currents and butanethiol concentrations by cyclic voltammetry and differential pulse voltammetry. As a proof of concept, the glassy carbon electrode was applied to determine the butanethiol molecule in an aviation biokerosene sample. The results obtained showed that this electrode has remarkable accuracy when applied toward the determination of butanethiol. [Figure not available: see fulltext.].
Keywords: Aviation biokerosene; Butanethiol; Contaminant; Electrochemical behavior; Glassy carbon electrode